Optimization of wavy fin‐and‐elliptical tube heat exchanger using CFD, multi‐objective genetic algorithm and radical basis function - Yu, Chao; Xue, Xiangyao; Shi, Kui; Wang, Renhao; Zhang, Lei; Shao, Mingzhen (Energy science & engineering, 2021)
This article presents an accurate and efficient optimization method for heat exchanger. The structure of the original heat exchanger was optimized by combining LHS sampling, CFD simulation, radical basis function, and multi‐objective optimization. Since the Colburn factor j and the friction factor f are a pair of conflicting goals, so the multi‐objective optimization is adopted. The optimization results showed that the Colburn factor j increased by 5.43% and the friction factor f decreased by 23.31%, indicating that the optimized structure had higher heat transfer efficiency and lower resistance performance. The heat transfer mechanism and optimization effect of heat exchanger are explained by using the field synergy principle, which provides a theoretical basis for the structural design optimization of heat exchanger. This paper presents an accurate and efficient optimization method for heat exchanger. The structure of the original heat exchanger was optimized by combining LHS sampling, CFD simulation, radical basis function, and multi‐objective optimization. Since the Colburn factor j and the friction factor f are a pair of conflicting goals, so the multi‐objective optimization is adopted. The optimization results showed that the Colburn factor j increased by 5.43% and the friction factor f decreased by 23.31%, indicating that the optimized structure had higher heat transfer efficiency and lower resistance performance. The heat transfer mechanism and optimization effect of heat exchanger are explained by using the field synergy principle, which provides a theoretical basis for the structural design optimization of heat exchanger.